2009
DOI: 10.1021/jp904989s
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties and Ionic Conductivity of Imidazolium Bis(trifluoromethanesulfonyl)imide Dicationic Ionic Liquids

Abstract: We report on the thermal and transport properties of new dicationic ionic liquids. The new ionic liquids are based on the bis(trifluoromethanesulfonyl)imide [NTf(2)](-) anion and a cation that contains two imidazolium rings, connected by either a pentane or a decane hydrocarbon chain and different side groups. We have investigated the conductivity and the thermal properties by dielectric spectroscopy and differential scanning calorimetry, respectively. Our results show that the length of the alkyl chain on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 19 publications
3
61
0
Order By: Relevance
“…The percent of the mass loss at different temperatures is listed in Table 2. 19 or pyridinium ring 22 of the ILs result in difference of physical properties such as density, viscosity, conductivity, glass transition temperature, and so on. That suggests the methyl in the meta position of …”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The percent of the mass loss at different temperatures is listed in Table 2. 19 or pyridinium ring 22 of the ILs result in difference of physical properties such as density, viscosity, conductivity, glass transition temperature, and so on. That suggests the methyl in the meta position of …”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[94][95][96][97][98][99] In one of the important reports, Buchner and Hefter mentioned that DRS has long been neglected as a tool for the investigation of the structure and dynamics of electrolyte solutions despite its immense abilities to quantify many aspects of ion-ion and ion-solvent interactions. [94][95][96][97][98][99] In one of the important reports, Buchner and Hefter mentioned that DRS has long been neglected as a tool for the investigation of the structure and dynamics of electrolyte solutions despite its immense abilities to quantify many aspects of ion-ion and ion-solvent interactions.…”
Section: Dielectric Relaxation Spectroscopymentioning
confidence: 99%
“…Pitawala et al 98 reported on the thermal and transport properties of new dicationic ionic liquids based on bis(trifluoromethanesulfonyl)imide [NTf 2 ] À anion and a cation that contains two imidazolium rings, connected by either a pentane or a decane hydrocarbon chain and different side groups using dielectric spectroscopy along with differential scanning calorimetry. It is highlighted by the authors that the length of the alkyl chain on the cation has no, or only weak, influence on the glass transition temperature, T g , whereas the presence of rigid aromatic side groups has a strong influence, increasing T g .…”
Section: Dielectric Relaxation Spectroscopymentioning
confidence: 99%
“…[37] Comparative data of other DCILs is very limited, but in contrast to previously reported ILs, the conductivities of these new compounds are higher. [13,46,47] For use of readers in the analytical chemistry field, conductivity experiments were also performed. The variation of conductivities was monitored as a function of molar fraction of methanol in the IL.…”
Section: Characterization In Liquid and Solid Statementioning
confidence: 99%